2023
DOI: 10.3390/insects14080695
|View full text |Cite
|
Sign up to set email alerts
|

Different Tea Germplasms Distinctly Influence the Adaptability of Toxoptera aurantii (Hemiptera: Aphididae)

Abstract: Aphids are typical phloem-sucking insect pests. A good understanding regarding their feeding behavior and population dynamics are critical for evaluating host adaptation and screening of aphid-resistant resources. Herein, the adaptability of Toxoptera aurantii (Boyer) (Hemiptera: Aphididae) to different hosts was evaluated via electropenetrography and an age-stage, two-sex life table on six tea germplasms: Zikui (ZK), Zhongcha108 (ZC108), Zhongcha111 (ZC111), Qianmei419 (QM419), Meitan5 (MT5), and Fudingdabaic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…'Huangjinya' is a novel chlorophyll-de cient albino cultivar that is susceptible to common pests of tea plants (e.g., E. onukii and Toxoptera aurantii) (Tian et al 2018;He et al 2023). 'Fuding white tea' is more suitable for herbivorous insects (e.g., Dendrothrips minowai, T. aurantii, and E. onukii) due to its high free amino acid content (Lu et al 2023). Although the nutritional level of plants often affects their suitability and resistance to herbivorous insects, insects search for and locate distant host plants using their sense of smell and vision in the early stages of pest infestation (Bruce et al 2005(Bruce et al , 2011.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…'Huangjinya' is a novel chlorophyll-de cient albino cultivar that is susceptible to common pests of tea plants (e.g., E. onukii and Toxoptera aurantii) (Tian et al 2018;He et al 2023). 'Fuding white tea' is more suitable for herbivorous insects (e.g., Dendrothrips minowai, T. aurantii, and E. onukii) due to its high free amino acid content (Lu et al 2023). Although the nutritional level of plants often affects their suitability and resistance to herbivorous insects, insects search for and locate distant host plants using their sense of smell and vision in the early stages of pest infestation (Bruce et al 2005(Bruce et al , 2011.…”
Section: Discussionmentioning
confidence: 99%
“…In tea plantations, there are observable differences in the occurrence of A. spiniferus on four tea cultivars. 'Huangjinya' and 'Fuding white tea' are more susceptible and suitable for A. spiniferus (Tian et al 2018;Lu et al 2023;He et al 2023), while 'Baiye No. 1' and 'Longjing 43' are common resistant cultivars (Liang et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of the EPG and population parameters indicated that QC1 and QC10 exhibited strong resistance to T. aurantii, whereas HJY was susceptible to attack by T. aurantii. There have been previous reports on the resistance of different tea germplasms to T. aurantii; however, the germplasm materials used by different researchers exhibit marked variation [17,44].…”
Section: Discussionmentioning
confidence: 99%